The cloud computing systems’ adoption in the higher education sector in Oman in light of the COVID-19 pandemic - Salim Al-Hajri; Abdelghani Echchabi; Abdullah Mohammed Ayedh; Mohammed Mispah Said Omar (International Journal of Evaluation and Research in Education (IJERE), 2021)
The objective of the research was to find out the key factors that influence the acceptance and usage of cloud computing systems in the Omani higher education sector, with special emphasis on the COVID-19 outbreak. For this purpose, a quantitative research approach was conducted where 200 students from several Omani higher education institutions were surveyed, and by using Partial Least Square (PLS) to analysis the collected data. The findings revealed that the intention to use cloud computing in this context is significantly dependent on its perceived ease of use, usefulness, perceived reliability and responsiveness. It is noteworthy that this is one of the early studies that address the subject of cloud computing usage during times of crises, and specifically the COVID-19 outbreak. As such, it provides significant contributions in the area of technology adoption.